Investigating Motor Preparatory and Initiation Processes in Parkinson’s Disease Using Transcranial Direct Current Stimulation and Startle - Kami, Aline Tiemi (Université d'Ottawa / University of Ottawa, 2020)
Parkinson’s Disease is a slowly progressing neurodegenerative process that is a result of a basal ganglia (BG) dysfunction caused by the death of dopaminergic neurons in the substantia nigra which could lead to difficulties in planning, initiating, and executing movement. One technique for studying movement preparation and initiation is the use of a Startling Acoustic Stimulus (SAS), which has been associated with changes in the movement processing in PD. Transcranial direct current stimulation (tDCS) has been used to modulate cortical excitability and neuroplasticity in humans, providing a potential method to improve motor performance in PD. As such, the purpose of the experiment was to investigate the potential benefits of tDCS applied over the primary motor area (MI) and supplementary motor area (SMA) associated with SAS paradigm to improve preparation and initiation of the movement in individuals with PD. Eleven individuals with PD completed two simple reaction time (RT) tasks, a button-press task (BU) and an elbow extension task (EX) and underwent to a bradykinesia assessment, before and after application of tDCS. Three tDCS testing sessions (Anodal-MI; Anodal-SMA; Sham) were carried-out separated by 48 hours to ensure a complete washout of any residual effects. Results from this experiment reinforce previous findings indicating that following a SAS, participants were able to elicit the prepared motor response in significantly shorter latencies, and movement time and time to peak displacement were improved as well. Additionally, the results also suggest that the premotor RT can be facilitated by tDCS applied over SMA in non-SAS condition. This is indicative that any potential increase in cortical excitability induced by tDCS was able to promote changes in the neural tissue which might have influenced the activation of structures and pathways involved in preparation and initiation – in particular a basal ganglia-thalamo-cortical pathway. We suggest that stimulation of the SMA with anodal-tDCS using simple RT task as strategy can be applied to improve preparatory and initiation processes in individuals with PD.
Keywords: Parkinson’s disease; Supplementary motor area; tDCS; Movement preparation